The Impact of Female Top Management Team Representation on a Firm's Supplier Orientation and Performance - Gligor, David; Kashmiri, Saim; Golgeci, Ismail (SAGE Publications, 2024)
The role and impact of females in supply chain management have received insufficient attention in extant research. In addition, research investigating the relationship between upper-echelon leadership and supply chain phenomena is extremely scant. To address these limitations, we collected archival data from 433 publicly traded Fortune 500 firms from 2007 to 2015 (3464 firm-year observations) and analyzed them using fixed-effect regressions. Our findings indicate that female top management team representation directly and positively influences a firm's supplier orientation. This influence of female representation is attenuated for firms that have a Chief Supply Chain Officer present in their top management team and for firms operating in environments characterized by high dynamism and low munificence. Furthermore, our findings show that supplier orientation mediates the impact of female top management team representation on firm performance. We put forth several interesting theoretical and managerial contributions. Most importantly, we hope that our findings, highlighting the positive impact of female executives on supplier orientation and providing additional evidence regarding women's managerial capabilities, will contribute towards eliminating bias and discrimination faced by women in the area of supply chain management and business in general.
Keywords: Supplier orientation; Female representation; Top management team; Chief supply chain officer